Simulation of Spherulite Growth Using a Comprehensive Approach to Modeling the First-Order Isotropic/Smectic-A Mesophase Transition (Communications in Computational Physics, 2018)
A comprehensive modeling and simulation study of the first-order isotropic/smectic-A transition is presented and applied to phase diagram computationand two-dimensional spherulite growth. An approach based on nonlinear optimization,that incorporates experimental data (from 12CB, dodecyl-cyanobiphenyl), is usedto determine physically realistic model parameters. These parameters are then used inconjunction with an optimized phase diagram computation method. Additionally, atime-dependent formulation is presented and applied to the study of two-dimensionalsmectic-A spherulite growth. These results show the growth kinetics and defect dynamicsof nanoscale smectic-A spherulite growth in an isotropic phase with an initiallyradial layer configuration.